Targeting Multiple Mitochondrial Processes by a Metabolic Modulator Prevents Sarcopenia and Cognitive Decline in SAMP8 Mice - Dario Brunetti; Dario Brunetti; Emanuela Bottani; Emanuela Bottani; Agnese Segala; Silvia Marchet; Fabio Rossi; Fiorenza Orlando; Marco Malavolta; Michele O. Carruba; Michele O. Carruba; Costanza Lamperti; et al. (Frontiers Media S.A., 2020)
The age-dependent declines of skeletal muscle and cognitive functions often coexist in elderly subjects. The underlying pathophysiological mechanisms share common features of mitochondrial dysfunction, which plays a central role in the development of overt sarcopenia and/or dementia. Dietary supplementation with formulations of essential and branched-chain amino acids (EAA-BCAA) is a promising preventive strategy because it can preserve mitochondrial biogenesis and function. The senescence-accelerated mouse prone 8 (SAMP8) is considered an accurate model of age-related muscular and cognitive alterations. Hence, we aimed to investigate the progression of mitochondrial dysfunctions during muscular and cognitive aging of SAMP8 mice and to study the effects of a novel EAA-BCAA-based metabolic modulator on these changes. We evaluated body condition, motor endurance, and working memory of SAMP8 mice at 5, 9, 12, and 15 months of age. Parallel changes in protein levels of mitochondrial respiratory chain subunits, regulators of mitochondrial biogenesis and dynamics, and the antioxidant response, as well as respiratory complex activities, were measured in the quadriceps femoris and the hippocampus. The same variables were assessed in 12-month-old SAMP8 mice that had received dietary supplementation with the novel EAA-BCAA formulation, containing tricarboxylic acid cycle intermediates and co-factors (PD-0E7, 1.5 mg/kg/body weight/day in drinking water) for 3 months. Contrary to untreated mice, which had a significant molecular and phenotypic impairment, PD-0E7-treated mice showed preserved healthy body condition, muscle weight to body weight ratio, motor endurance, and working memory at 12 months of age. The PD-0E7 mixture increased the protein levels and the enzymatic activities of mitochondrial complex I, II, and IV and the expression of proliferator-activated receptor γ coactivator-1α, optic atrophy protein 1, and nuclear factor, erythroid 2 like 2 in muscles and hippocampi. The mitochondrial amyloid-β-degrading pitrilysin metallopeptidase 1 was upregulated, while amyloid precursor protein was reduced in the hippocampi of PD-0E7 treated mice. In conclusion, we show that a dietary supplement tailored to boost mitochondrial respiration preserves skeletal muscle and hippocampal mitochondrial quality control and health. When administered at the early onset of age-related physical and cognitive decline, this novel metabolic inducer counteracts the deleterious effects of precocious aging in both domains.